Dynamic Inventory Policy with Varying Stochastic Demands - Karlin, Samuel (Management Science, 1960)
A dynamic inventory model is formulated in which the demand distributions may change from period to period. The optimal policy at each stage is characterized by a single critical number which also could vary in successive periods. The dependence of the critical numbers as a function of stochastic ordering amongst distributions is developed under various conditions. Most of the studies are conducted under the assumption of linear purchasing cost. In §3 the possibility of convex purchasing cost is allowed.